Pemanfaatan Media Pembelajaran Berbasis Teknologi dalam Pembelajaran PPKn di Kelas XI SMA N 1 Lubuk Basung - Rahmi, Rika; Indrawadi, Junaidi; Ananda, Azwar; Montessori, Maria (Journal of Civic Education, 2024)
This study explores the application of technology-based learning media in Pancasila and Civic Education (PPKn) for eleventh-grade students at SMA N 1 Lubuk Basung, Agam Regency, West Sumatra. Employing a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. Data validity was ensured through source triangulation, while analysis followed the steps of data reduction, data display, and conclusion drawing. Findings indicate that technology-based media have been integrated into PPKn instruction in this classroom, with teachers skillfully managing their use despite challenges. Key obstacles include time required for device setup, limited Wi-Fi access, and student-reported issues, such as distracting shadows on PPT slides, unclear text, and low video volume. To address these challenges, teachers take measures such as preparing media in advance to maximize instructional time, providing alternative media options if needed, ensuring internet access through personal mobile data for hotspotting, incorporating student feedback into media evaluation, and participating in school-provided training on effective technology use in teaching. This research is limited to only one school in Agam Regency, West Sumatra, so the same problems may not be found in other places, for example in urban areas, obstacles such as internet access are not a major problem.